2018
DOI: 10.4317/jced.54470
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral findings and laboratory tests in children and adolescents undergoing dialysis: A cross- sectional study

Abstract: BackgroundDiagnosis of oral complications in the dialysis patients is important to prevent potential infections. The aim of this cross-sectional study was to compare oral findings in dialysis patients with healthy individuals and determination of the correlation of these findings and laboratory tests.Material and MethodsIn this cross-sectional study, DMFT, dmft, DI , CI , OHIS , PI, GI and enamel defects were evaluated in 25 hemodialysis patients, 30 peritoneal dialysis patients and 26 healthy individuals. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Патологичните находки, ангажиращи компонентите на пародонталния апарат, се асоциират със завишените стойности на урея не само на системно ниво, но и локално в слюнчен субстрат, което е предиспозиращ фактор за интензивно абнормно натрупване на плака и зъбен камък, респ. влошаване на гингивалното здраве (28,29,30,31).…”
Section: обсъжданеunclassified
“…Патологичните находки, ангажиращи компонентите на пародонталния апарат, се асоциират със завишените стойности на урея не само на системно ниво, но и локално в слюнчен субстрат, което е предиспозиращ фактор за интензивно абнормно натрупване на плака и зъбен камък, респ. влошаване на гингивалното здраве (28,29,30,31).…”
Section: обсъжданеunclassified
“…It has been observed that 5 to 10 million people die each year from kidney disease [1][2][3][4]. Chronic renal failure (CRF) is a progressive disease characterized by the gradual destruction of nephrons and a consequent reduction of kidney function occurring over a few months or years [5][6][7]. With the development of that process, the glomerular filtration rate reduces below 15 mL/min, leading to accumulation of metabolic such as urea and creatinine in serum [4,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Analyze the flow rate, pH and biochemical composition (urea, creatinine, and calcium) that demonstrate identifiable and regular changes from pre-dialysis to post-dialysis states can enable necessary monitoring of dialysis efficacy and the level of renal function in patients with CRF [9,14]. Ninety percent of patients with CRF have oral complications caused by changes in bones and soft tissues of mouth [7,16]. Such oral complications alter salivary composition reflecting at systemic levels.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases there is anemia related to this disease resulting from decreased erythrocyte production, iron sequestration, protein malnutrition (from lack of appetite and being on a diet not meeting their protein needs to meet the ability to make hemoglobin) and loss of blood (related to uremic gastritisinduced gastrointestinal bleeding), hence constant blood sampling may worsen already existing anemia. (9) Unfortunately, collection of blood samples is an invasive practice that may comprise some hazard to the health of medical staff and patients as well as being a source of discomfort in a number of populations and situations, especially when dealing with pediatric population or special needs patients. Moreover, the need for special equipment and well trained personnel makes the sampling process very expensive.…”
Section: Introductionmentioning
confidence: 99%